Human immunodeficiency virus type 1 recombinant B/G subtypes circulating in Coimbra, Portugal. - Duque, V (2003)
An increasing prevalence of HIV-1 non-B variants is being noticed in several European regions, particularly in countries such as Portugal, which have closer contacts with African endemic areas, where multiple HIV subtypes cocirculate. HIV-1 subtyping by phylogenetic analyses of reverse transcriptase, protease and env (C2-V3) genomic regions was carried out in plasma collected from 18 HIV-1-infected subjects living in Coimbra, Portugal, and suspected to be infected with non-B variants. Three (16.7%) subjects carried recombinant B/G viruses (BV3/BRT/Gpro; GV3/URT/Bpro; AV3/GRT/Bpro), whereas all the remaining individuals were infected with HIV-1 subtype B. This is the first report of recombinant B/G subtypes in Portugal.